Ni(II) Interactions in Boreal Paenibacillus sp., Methylobacterium sp., Paraburkholderia sp., and Pseudomonas sp. Strains Isolated From an Acidic, Ombrotrophic Bog - Knuutinen, Jenna; Bomberg, Malin; Kemell, Marianna; Lusa, Merja (Frontiers in Microbiology, 2019)
The uptake of nickel (Ni(II)) by Peanibacillus sp., Methylobacterium sp., Paraburkholderia sp. and Pseudomonas sp. strains isolated from a boreal bog was studied using batch experiments. All strains removed Ni(II) from the solution and the uptake efficiency was affected by the nutrient source, incubation temperature, time and pH. As highest Ni uptake (with a maximum Kd of 1890 L/kg DW) was recorded for the Pseudomonas sp. strains, these bacteria were used in the following protein expression (SDS-PAGE and MALDI-TOFF), TEM and EDS experiments. In addition, Freundlich and Langmuir sorption isotherms were determined. In the Ni(II) treated cells, dense crystalline intra-cellular accumulations were observed in TEM examinations, which were identified as Ni accumulations using EDS. SDS-PAGE and MALDI-TOFF spectra of Ni(II) treated cells showed several changes in the protein profiles, which can indicate active accumulation of Ni in these bacteria. Concurrently, we observed Ni(II) uptake to follow Freundlich and Langmuir isotherms, suggesting straight cellular biosorption in addition to the intra-cellular accumulation. The role of cellular (cell membrane and cell wall) functional groups involved in Ni(II) binding were therefore studied using Fourier transformation infrared spectroscopy (FTIR). These analyses supported the potential role of the alcoholic hydroxyl, carboxyl and amine groups in Ni(II) binding in these bacteria, therefore suggesting two different Ni(II) uptake mechanisms; (i) intra-cellular accumulation (possibly connected to detoxification of Ni(II)), and (ii) straight biosorption on cell membrane/wall functional groups.